Strengthening Integrity and Fraud Awareness in Preventing Fraud During the Covid-19 Pandemic - Ramadhan, Dona (Asia Pacific Fraud Journal, 2022)
The Covid-19 pandemic has impacted almost all socio-economic and business aspects. Changes in interaction patterns and a decrease in income lead to a higher potential for fraud risk. Management needs to take effective ways to mitigate fraud, especially fraud prevention as the most efficient strategy. This paper aims to explore and manage new challenges in terms of fraud risk related to the Fraud Triangle in non-digital financing companies. Using a quantitative approach, this study examines the effect of integrity and fraud awareness on fraud prevention according to the perception of the fraud detection team. 67 samples were collected and processed through PLS regression. The results show that R2 value is 0.592; integrity t-score is 3.315, p-value is 0.001; Fraud Awareness t-score is 2.119, p-value is 0.0341. Thus, integrity and fraud awareness have a positive and significant effect on fraud prevention in non-digital financing companies. However, there are some limitations that need to be investigated further, such as measurements for other fraud prevention strategies, other financial institutions, and other business industries that have been negatively affected by the Covid-19 pandemic.